Transfer Pricing in the Spotlight: An Analysis of the Role of Taxes, Profitability, Tunneling Incentives, and Independent Commissioners - Subagio, Subagio; Ardianto, Hendra Prasetya (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Transfer pricingis a financial strategy that companies can use to optimize tax structures and operational efficiency. However, this practice also has the potential to pose tax compliance risks and poor governance. This phenomenon is increasingly relevant in the mining sector, which has a complex business structure and transactions. This study aims to analyze the influence of taxes, profitability, tunneling incentives, and independent commissioners on companies' transfer pricing decisions. This study uses a quantitative method with a panel data regression analysis model, random effects model (REM). The research sample consisted of mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023, selected through purposive sampling. The results show that all four independent variables simultaneously influence transfer pricing. Partially, the results indicate that profitability and independent commissioners have a significant negative effect on transfer pricing, while taxes and tunneling incentives have no effect. This research is expected to enrich the literature on transfer pricing, especially in the Indonesian context.